(untitled) (Semiárida, 2020)
Standig crop of Pappophorum caespitosum "pasto blanco" grassland was determined in the southeastern of La Pampa Province, Dpto. Caleu Caleu, Ea. Los Guadales. Lat. 38°13’S - Long. 64°18’ W. At the end of autumn (june) the grassland reached 315 gMS/m2. Pappophorum caespitosum the principal specie totalized 248,6 gMS/m2. In spring (november) Medicago minima "Trebol de carretilla", Erodium cicutarium "alfilerillo" y Pelletiera serpyllifolia three annual species gave only 61.4 gMS/m2. The vegetation cover was middle in the grassland during all the year-, "Pasto blanco", Setaria pampeana "cola de zorro" y Stipa ambigua "paja vizcachera" had 100 % of frecuency